Evaluation of bone regenerative capacity in rats claverial bone defect using platelet rich fibrin with and without beta tri calcium phosphate bone graft material - Walid Ahmed Abdullah (Saudi Dental Journal)
Aim: To compare bone regeneration in noncritical rat calvarial bone defects filled with platelet-rich fibrin (PRF), alone or combined with beta-tricalcium phosphate (β-TCP), using micro-computed tomographic (MCT) evaluation. Animals and methods: Two calvarial bone defects were created in each of 45 male Sprague–Dawley rats (age: 20–22 weeks, weight: 350–450 g), using a dental trephine with an external diameter of 3 mm. The 90 defects were randomly allocated among three groups, each containing 30 unilateral defects in a total of 30 rats. Defects in the control group were allowed to heal spontaneously. Defects in the PRF group received PRF alone. Defects in the PRF/β-TCP group received PRF mixed with β-TCP in a 50⧹50 percentage. Nine animals (three per group) were killed after 1, 2, 3, 4, and 6 postoperative weeks, and 18 calvarial defects from each period were analyzed for new bone formation and bone mineral density using MCT. Results were compared by a one-way Analysis of Variance with the POST HOC Least Significant Difference test. Results: The volume and mineral density of bone formed in the control group were significantly different from those of the other two groups. Greater bone regeneration was observed in defects receiving PRF with β-TCP compared to defects receiving PRF alone in the first 2 weeks (P < 0.001). However, differences in the volume and density of newly formed bone between the PRF and PRF/β-TCP groups were not significant at 3, 4, and 6 postoperative weeks (P > 0.005). Conclusion: The addition of β-TCP to PRF significantly improved bone regeneration in the first 2 weeks after surgery. Although the differences between results with and without the addition of β-TCP to PRF were statistically insignificant from weeks 3 to 6, it was nevertheless apparent that the group receiving the combination showed better results. We suggest a synergistic mechanism for this effect. Keywords: Platelet rich fibrin, BTCP